(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
The rapid evolution of financial instruments has transformed how companies manage their capital, make strategic decisions, and enhance corporate governance. In particular, the rise of innovative financial tools such as blockchain, green bonds, tokenized assets, and ESG-linked securities has introduced new dynamics into the corporate governance landscape. This paper explores the relationship between innovative financial instruments and corporate governance, examining how these tools can reshape decision-making processes, improve transparency, and enhance shareholder value. By analyzing existing research, real-world case studies, and expert opinions, the paper offers insights into how companies can integrate these innovations to improve governance structures, risk management, and overall organizational performance.